2020
DOI: 10.1177/1358863x20952856
|View full text |Cite
|
Sign up to set email alerts
|

Trends and perioperative outcomes of patients with human immunodeficiency virus (HIV) undergoing lower extremity revascularization

Abstract: The development of highly active antiretroviral therapy (HAART) has significantly improved the life expectancy of patients with human immunodeficiency virus (HIV), but has led to the rise of chronic conditions including peripheral artery disease (PAD). However, trends and outcomes among patients with HIV undergoing lower extremity revascularization are poorly characterized. The aim of this study was to investigate the trends and perioperative outcomes of lower extremity revascularization among patients with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Data on in-hospital outcomes immediately following PVI among PLWH in the National Inpatient Sample did not demonstrate increased rates of in-hospital amputation or mortality, but did not explore events after discharge. 21,22 Multiple factors likely contribute to the increased risk of MALE observed among PLWH in our population. Our data are consistent with prior studies which have reported a high prevalence of traditional cardiac risk factors among PLWH with suboptimal control of modifiable contributors to disease, such as smoking.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Data on in-hospital outcomes immediately following PVI among PLWH in the National Inpatient Sample did not demonstrate increased rates of in-hospital amputation or mortality, but did not explore events after discharge. 21,22 Multiple factors likely contribute to the increased risk of MALE observed among PLWH in our population. Our data are consistent with prior studies which have reported a high prevalence of traditional cardiac risk factors among PLWH with suboptimal control of modifiable contributors to disease, such as smoking.…”
Section: Discussionmentioning
confidence: 93%
“…Data on in-hospital outcomes immediately following PVI among PLWH in the National Inpatient Sample did not demonstrate increased rates of in-hospital amputation or mortality, but did not explore events after discharge. 21,22…”
Section: Discussionmentioning
confidence: 99%